ACTIVITY ON MALAY SQUARE’S OPEN SPACE AS A NODE OF TANJUNGPINANG CITY - Septy Karmawan (Universitas Riau Kepulauan, 2015)
Seaside is an open space as a public gathering place various kinds of activities whose existence was known by the City Community open space public seaside city tanjungpinang, because this is not only a place of gathering of all people from all over the city, where people meet people from various sorts of places in the area to do the activities they want in the open space while enjoying the ambiance as well as a lounge and night sights